A real-time measure of business conditions in Malta - Reuben Ellul (Central Bank of Malta, 2016)
This paper outlines the structure for a high frequency measure of economic activity in Malta, with the ability of identifying turning points and changes in activity in real time. An array of flow and stock data is applied, measured at mixed frequencies. A dynamic factor model then filters the data and constructs a high frequency business conditions index (BCI). The framework is based on a study by Aruoba, Diebold and Scotti (2009). In this paper, their prototype example is extended to include extra monthly variables.
Keywords: E32; E37; C01; C22; 330